Clinical application of an intelligent oropharyngeal swab robot: implication for the COVID-19 pandemic - Li, Shao-Qiang (Eur Respir J, 2020)
Clinical application of the safety and effectiveness of an intelligent oropharyngeal-swab robot, and its implication for the COVID-19 pandemic https://bit.ly/2BUsV55